Estimated biomass of demersal flshes off Saurashtra coast - Vivekanandan, E; Gopal, C (Indian Journal of Fisheries, 2011)
Trawl survey conducted at regular inter* vals for a long period provides valuable information on the status of the biomass and spatial and groupwise distribution of fishes, thuis enabling formulation of fishery management policies. There are only a few attempts to estimate the fish biomass of the nordiwest coast of India (Bapat et al. 1982, Rao and Kunjipalu 1989). An analysis was, thaÂ«fore, done to strengthen the existing knowledge on the demersal fish bicMniass along the Saurashtra coast